OPTIMASI PARAMETER 3D PRINTING TERHADAP WAKTU DAN WARPING DENGAN PENDEKATAN METODE TAGUCHI - Mase Hideaki; Agus Halim; Erwin Siahaan (Program Studi Teknik Mesin Universitas Tarumanagara, 2022)
Fused Deposition Modeling (FDM) is one of the most popular 3D printing technology that used at academic and business purposes due to the easiness of the manufacture process that it held. But, one of the most major problems that usually occur in the industry is the frequentness of damaged and deficiency on the result of printing, especially when it is printed using the ABS filament. Although, ABS is one of the filaments which has a lower cost compared to others, but has a bigger value per gram on the printing sectors compared to PLA filaments. It could be a good business prospect if it can be handled on the problems. Therefore, the knowledge on how to prevent the problems, and finding an efficiency on the various of infill pattern, would be one of the key of success in this industry. In this article, a research on finding optimum parameters against the time and quality of the product using the Taguchi method, and also ASTM D-638 is also needed to find the best infill pattern against the tensile strength that an ABS filament have on the mechanical properties. As a result, the parameters, nozzle temperature and bed temperature have a small impact on producing time, but have a greater impact on the quality of printing product. Besides, the infill pattern which has the biggest tensile strength on smaller density is Trihexagon. Meanwhile, the Lines infill has the biggest standard of deviation, which endure the most stress on the bigger density compared to Triangles and Trihexagon.